2017
DOI: 10.1080/19371918.2016.1268990
|View full text |Cite
|
Sign up to set email alerts
|

Information Poverty and Reproductive Healthcare: Assessing the Reasons for Inequity between Income Groups

Abstract: It is commonly known that in the United States women who are low income do not access reproductive healthcare services and information with the same reliability and regularity of women who are higher income. A qualitative research approach was undertaken to assess the root cause of this disparity. In-depth semistructured interviews were conducted with 15 women divided among socioeconomic lines. The primary barriers to care for women who are low income are clinical staff attitudes, knowledge of care available a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…This is in accordance with previous studies which found that knowledge about treatment was a barrier of utilisation and access for lower-SES patients, for example, to optimal oesophageal cancer care or reproductive healthcare. 23 24 Especially in low-SES patients, it is well known that lack of information and knowledge results in low utilisation. 25 26 This is probably due to the fact that patients of lower SES are generally given less information in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous studies which found that knowledge about treatment was a barrier of utilisation and access for lower-SES patients, for example, to optimal oesophageal cancer care or reproductive healthcare. 23 24 Especially in low-SES patients, it is well known that lack of information and knowledge results in low utilisation. 25 26 This is probably due to the fact that patients of lower SES are generally given less information in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Of the articles that were retrieved, cancer prevention (Akhtari-Zavare, Ghanbari-Baghestan, Latiff, & Khaniki, 2015;Hay, Orom, Kiviniemi, & Waters, 2015;Jung, Senthilselvan, & Salopek, 2011;Ross et al, 2011) and sexual health (Buhi, Daley, Fuhrmann, & Smith, 2009;Davis, 2014;Mitchell, Ybarra, Korchmaros, & Kosciw, 2014;Zimmerman, 2017) were primary foci of attention. Articles that fit into this context predict that higher knowledge levels about a medical condition or practice will result in positive behaviour change (Akhtari-Zavare et al, 2015;Deng et al, 2015;Zimmerman, 2017), although in several articles this information is implicit instead of stated (Finney- Haluza, Naszay, Stockinger, & Jungwirth, 2017;Rutten, Augustson, Doran, Moser, & Hesse, 2009). A number of articles explored the specific predictors or antecedents to HISB with the intention of behaviour change (Haluza et al, 2017;Hay et al, 2015;Ross et al, 2011).…”
Section: Hisb In the Context Of Behaviour Change And Preventive Behavmentioning
confidence: 99%
“…Examination of source use based on personal and socioeconomic variables is also well represented in this literature selection. These may include age (Geana et al, 2011;Kratzke et al, 2013), ethnicity (Jackson, Botelho, Joseph, & Tennstedt, 2013), education (Feinberg et al, 2016), income (Zimmerman, 2017), efficacy belief (Lee & Kim, 2015) or health literacy (Lubetkin et al, 2015). Research that falls into the description of discretionary actions in this review explored activities such as the motivation to share knowledge compelling searching (Roettl et al, 2016), how intimidated low literacy level women feel interacting with health care providers and if this negatively impacts their exchange (Patel & Dowse, 2015) and the relationship between insurance status and offline versus online seeking behaviour (Saulsberry et al, 2014).…”
Section: Characteristics Of Hisbmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the knowledge gap hypothesis [37], groups trapped in information poverty are at a disadvantage in terms of information absorption, creating an information gap with other groups, and this gap will grow wider. The information gap and information poverty are closely related to economic poverty [38,39]. Information poverty and economic poverty are mutually causal, and people with information poverty often fall into the cycle of "information poverty-economic poverty-information poverty" [39].…”
Section: Literature Reviewmentioning
confidence: 99%